Educational Assimilation Strategies in Building an Inclusive Civilization in the Midst of Pakistan's Divided Society: A Systematic Literature Review - Fauzan Addinul Jihad; Mutohharun Jinan (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to analyze the strategies of assimilation of education in Pakistan to build an inclusive civilization in a divided society while identifying knowledge gaps in the existing literature. The core problem lies in the fragmented education system, which creates "educational apartheid" and exacerbates social segregation based on ideology and socio-economic class. The method used is Systematic Literature Review (SLR) following the PRISMA guidelines, synthesizing 10 final articles drawn from the Scopus database between 2015 and 2025. The findings reveal that the assimilation strategy in Pakistan is dominated by a top-down approach through the instrumentalization of religion and the standardization of the Single National Curriculum (SNC). However, this strategy proved ineffective because it fueled ethno-nationalist resistance, deepened sectarian divisions, and perpetuated gender bias. This conclusion confirms that coercive assimilation fails to foster authentic social cohesion. Therefore, a paradigm shift towards an integrative model that accommodates the plurality of identities and deconstructs colonial legacies is essential to achieving a stable and inclusive civilization.